2009
DOI: 10.1073/pnas.0903060106
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Gal4 genetics for permanent gene expression mapping in zebrafish

Abstract: Combinatorial genetics for conditional transgene activation allows studying gene function with temporal and tissue specific control like the Gal4-UAS system, which has enabled sophisticated genetic studies in Drosophila. Recently this system was adapted for zebrafish and promising applications have been introduced. Here, we report a systematic optimization of zebrafish Gal4-UAS genetics by establishing an optimized Gal4-activator (KalTA4). We provide quantitative data for KalTA4-mediated transgene activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
322
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 276 publications
(327 citation statements)
references
References 30 publications
5
322
0
Order By: Relevance
“…Previously, an optimized Gal4/UAS system was established in zebrafish (Distel et al 2009). They compared the activator activity and toxic effect of three Gal4-VP16 activators, GalTA4, TA3, and TA2, which are different in the repeats of VP16 trans-activation domain (13-amino acid core sequence), and it was suggested that the TA4 is a relative highly efficient activator with low toxicity compared with TA2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, an optimized Gal4/UAS system was established in zebrafish (Distel et al 2009). They compared the activator activity and toxic effect of three Gal4-VP16 activators, GalTA4, TA3, and TA2, which are different in the repeats of VP16 trans-activation domain (13-amino acid core sequence), and it was suggested that the TA4 is a relative highly efficient activator with low toxicity compared with TA2.…”
Section: Resultsmentioning
confidence: 99%
“…To generate the mylpfa:EGFP transgenic construct, the mylpfa regulatory region was subcloned into the 4xKGFP plasmid (Distel et al 2009) containing the Tol2 transposon and the EGFP coding sequence using the SalI and EcoRI sites. To generate the mylpfa:Gal4 construct, the KalTA4 coding sequence from the 4xKaloop plasmid (Distel et al 2009) was subcloned into the mylpfa:EGFP construct using the EcoRI and NotI sites.…”
Section: Dna Constructs and 5′ Upstream Regulatory Region Cloningmentioning
confidence: 99%
See 2 more Smart Citations
“…All experiments were carried out using fertilized eggs from the fish line Tg(atoh1a:Gal4TA4) (line hzm2Tg) [6], crosses of Tg(atoh1a:Gal4TA4) with Tg(4xUAS-GFP) (hzm3Tg) [30], or wt brass.…”
Section: Methodsmentioning
confidence: 99%